2016
DOI: 10.1002/dneu.22424
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5 is required for the positioning and survival of GABAergic neurons in developing mouse striatum

Abstract: Cyclin-dependent kinase 5 (Cdk5) is a serine/threonine kinase, and its activity is dependent upon an association with a neuron-specific activating subunit. It was previously reported that Cdk5 mice exhibit perinatal lethality and defective neuronal positioning. In this study, they focused on the analysis of neuronal positioning of GABAergic neurons in the forebrain. Defective formation of the ventral striatum, nucleus accumbens, and olfactory tubercles was found in Cdk5 embryos. To further study this abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The dosage and activity of Cdk5 is tightly regulated in the brain [ 102 ]; in particular, p35 and p39 are both essential for Cdk5 activity and may be the principal activators of Cdk5 [ 103 ]. Cdk5 is involved in dendritic spine formation, is important in Purkinje cell migration and dendritic growth, and is required for formation of ventral striation; loss of Cdk5 causes GABAergic neuronal death in the developing mouse foetus, as shown in p35 cKO and p39 KO mice [ 104 , 105 , 106 ]. Cdk5 phosphorylation of the neural protein Synapsin III is needed to regulate neurite outgrowth and axonal elongation [ 107 ].…”
Section: Brain Development and Functionmentioning
confidence: 99%
“…The dosage and activity of Cdk5 is tightly regulated in the brain [ 102 ]; in particular, p35 and p39 are both essential for Cdk5 activity and may be the principal activators of Cdk5 [ 103 ]. Cdk5 is involved in dendritic spine formation, is important in Purkinje cell migration and dendritic growth, and is required for formation of ventral striation; loss of Cdk5 causes GABAergic neuronal death in the developing mouse foetus, as shown in p35 cKO and p39 KO mice [ 104 , 105 , 106 ]. Cdk5 phosphorylation of the neural protein Synapsin III is needed to regulate neurite outgrowth and axonal elongation [ 107 ].…”
Section: Brain Development and Functionmentioning
confidence: 99%
“…Although loss of 39 is not lethal, it attenuates overall Cdk5 activity in neurons as well as leads to aberrant axonal growth and impaired dendritic spine formation through affecting Cdk5 targets governing neuronal differentiation and network formation ( Li et al, 2016 ). In adult brain, emerging evidences have indicated that Cdk5 complex regulated multiple neuronal functions including neuronal survival, neurite and axon outgrowth, synaptic plasticity, neurotransmission ( Ye et al, 2014 ; Sasamoto et al, 2017 ; Takahashi et al, 2022 ). Because of its extensive and crucial roles in nervous system, the dysfunction of Cdk5 is critically involved in numerous neurological disorders such as neurodegenerative diseases, stroke, psychiatric disorders, pathological pain, epilepsy and so on.…”
Section: Introductionmentioning
confidence: 99%